A pilot, prospective, observational study to investigate the value of NGS liquid biopsies to predict tumor response after neoadjuvant chemo-radiotherapy in patients with locally advanced rectal cancer: The LiBReCa study. (1st June 2022) - Roesel, R; Epistolio, S; Saletti, P; De Dosso, S; Valli, M; Franzetti-Pellanda, A; Deantonio, L; Bigioggero, M; Spina, P; Popeskou, S G; Mongelli, F; Frattini, M; et al.
Abstract: Objective: Circulating tumor DNA (ctDNA) has been shown to correlate with therapy response in different types of cancer.Little is known about the value of liquid biospies in locally advanced rectal cancer (LARC) to select patients for non-operative management. Our aim was to explore the value of serial liquid biopsies for response monitoring after neo-adiuvant chemoradiation therapy (nCRT) in LARC. Methods: Twenty-five consecutive LARC patients undergoing long course nCRT therapy were included. Applying next-generation sequencing (NGS), we characterized DNA extracted from formalin-fixed paraffin embedded tissue (diagnostic biopsy and surgical specimen)and from plasma ctDNA collected at different time points: on the first and last day of radiotherapy (T0, Tend), at 4 (T4), 7 (T7) weeks after radiotherapy, at the day of surgery (Top) prior to resection, and 3–7 days after surgery (Tpost-op). At the day of surgery a mesenteric vein sample was also collected (Timv). The relationship between the ctDNA at those time-points and the Tumor Regression Grade (TRG) of the surgical specimen was statistically explored. Results: ctDNA was detected in 87% of samples at baseline but only in 13%, 10%, 25% and 17% at T4, T7, Top and Tpost-op respectively. Pathological complete response (TRG1) was not statistically associated with gradual negativization of ctDNA mutations in plasma samples obtained in the aforementioned time points compared to tissue biopsy. However a positive liquid biopsy at Top was significantly associated to no response to nCRT (TRG 4) . Conclusion: ctDNA evaluation by NGS technology was not a good marker for defining LARC patients that are more prone to develop complete response to nCRT, however persistence of ctDNA molecular alterations after this treatment could be a marker of poor-response.